Bibliometric Review: Elementary and Mathematics Education from Indonesian Authors - Edi Supriyadi; Sarah Inayah; Jarnawi Afgani Dahlan; Darhim Darhim (Profesi Pendidikan Dasar, 2022)
Several studies in the field of elementary education have examined the preparedness of elementary education to meet the challenges of the 4.0 industrial revolution. Unfortunately, there are currently no data that can be considered conclusive regarding the number of international publications pertaining to elementary education in Indonesia. The current study detailed the progress of elementary mathematics education research from the past to the present. Utilizing a literature review methodology, the study determined elementary mathematics education research trends in Indonesia. Then, a bibliometric analysis was conducted with the R package Biblioshiny to evaluate related articles in order to identify research trends, topics, and keywords. This study revealed that among all affiliations and authors, Sriwijaya University's Elementary Mathematics Education is the most influential. The term retrospective analysis currently leads the trend in elementary mathematics education research keyword usage